Peningkatan Literasi Menulis Teks Deskripsi Melalui E-LKPD Scan to Adventure - Wiguna, Arya Chandra; Abidin, Yunus; Muna Aljamaliah, S. Nailul (Universitas Muhammadiyah Surakarta, 2024)
This research concerns the development of E-LKPD scan to adventure to improving the descriptive text writing skills of fourth-grade elementary school students. Development research design utilizes D&D type 1 which focuses on product design, development, and evaluation. The results of the feasibility test and field test are presented on a scale of 1-4 where categories 1 (strongly disagree), 2 (disagree), 3 (agree), 4 (strongly agree). The results of material validation obtained a mode score of 3 which had the